The critical role of gut microbiota in obesity - Cheng, Zilu; Zhang, Li; Yang, Ling; Chu, Huikuan (Frontiers in Endocrinology, 2022)
Obesity is a global epidemic characterized by energy disequilibrium, metabolic disorder, fat mass development, and chronic low-grade inflammation, which remarkably affects the health state of individuals of all ages and strains socioeconomic system. The prevalence of obesity is rising with alarming rates and its etiology involves in complicate interplay of diet, genetic as well as environmental factors. The gut microbiota, as an important constituent of environmental factors, has been confirmed to correlate with the onset and progression of obesity. However, the specific relationship between obesity and the gut microbiota, and its associated mechanisms, have not been fully elucidated. In this review, we have summarized that the microbial diversity was remarkably decreased and the Firmicutes/Bacteroidetes ratio was remarkably increased in obesity, the altered gut microbiota and associated metabolites contributed to the progression of the disease by disrupting energy homeostasis, promoting lipid synthesis and storage, modulating central appetite and feeding behavior, as well as triggering chronic inflammation, and that the intentional manipulation of gut microbiota held promise as novel therapies for obesity, including probiotics, prebiotics, and fecal microbiota transplantation.